All Atom Motion Tree detects side chain-related motions and their coupling with domain motion in proteins - Ryotaro Koike; Motonori Ota (Biophysics and Physicobiology, 2019)
Structural changes of proteins are closely related with their molecular function. We previously developed a computational tool, Motion Tree (MT), to compare protein structures and describe structural changes using solely the Cα atoms. Here, we have extended MT to incorporate all heavy atoms to analyze side chain-related (SCR) motions. All Atom Motion Tree (AAMT) was applied to 76 proteins that exhibited a simple domain motion identified by MT. AAMT also detected 921 SCR motions. We examined the coupling of domain and SCR motions and classified the structural changes in terms of coupling. The statistical results indicated that it is common for coupled SCR motions to also couple with the domain motion. The classification correlates properties of domain motions and SCR motions. The AAMT results suggest that a large domain motion with a sizable domain boundary is accompanied by SCR motions composed of more than a single residue, which induces further couplings of SCR motions.